The effect of an educational intervention based on pender's health promotion model on treatment adherence in the patients with coronary artery disease - Forough Faroughi; Mohsen Shahriari; Mahrokh Keshvari; Farymah Shirani (Wolters Kluwer Medknow Publications, 2021)
Background: Increasing of hospitalization rates of Coronary Artery Disease (CAD) management have created major challenge for the health system. Poor adherence to treatment is one of the main reasons for treatment failure, prolongation of treatment, and increase care costs. The aim of this research was to determine the effect of educational intervention based on Pender's Health Promotion Model (HPM) on adherence in patients with CAD. Materials and Methods: This randomized controlled clinical trial was held in an educational hospital in Isfahan, Iran, February 2018-May 2019. Data were collected from 64 patients with CAD, before, 1 and 3 months after the intervention. The instrument used included treatment adherence questionnaire and a checklist Pender's HPM. The study group received dietary, exercise, and medication education based on Pender's HPM in four sessions which were held in 4 weeks. The control group received the routine educational program of the hospital. The data was analyzed using descriptive statistics, repeated measures ANOVA, independent t, Chi-square, and Mann-Whitney tests via SPSS software. Results: The mean score of treatment adherence was significantly different between two groups in one (z = 5.28, df = 2, p < 0.001) and three (z = 4.51, df = 2, p < 0.001) months after the intervention. The mean (SD) of treatment adherence in the study group was 139.82 (27.44) 3 months after the intervention. Conclusions: Educational intervention based on Pender's HPM is more effective on treatment adherence than the routine method in the patients with CAD. It is recommended to integrate the Pender's HPM as a nursing care program for these patients.